Evaluating stigma among infertile men and women in Iran - SJ Younesi; S Akbari-Zardkhaneh; Z Behjati Ardakani (JRI, 2006)
Introduction: Psycho-social aspects of physical disability may create more problems for the indi-vidual than the disability itself. The infertile may suffer from misjudgments or prejudices in different situations by their colleagues and relatives. All factors for this suffering can be evaluated in stigma settings which the infertile confront. In addition to these pathological settings, there are some opportunities which infertile people can enjoy for more adaptations with their social envi-ronments. The objective of this study was to become familiarized with different aspects of psycho- social life of the in fertile in the setting of Iranian culture. Materials & Methods: 268 fertile and infertile subjects were involved in this study from two different regions of Iran. Through a considerable number of interviews with infertile individuals in the pilot study, the styles of social interaction with people and also positive and negative cons-tructs related to their social lives were recognized. Utilizing a suitable instrument (Repertory grid) and factor analysis of scores, disability factors concerning social aspects of infertility were disco-vered. Moreover, regression analysis and t-test (p< .05) were used for the analysis of the data. Results: The statistical analysis including t-test, factor and regression analyses indicated that social comparison, as one of the sources for self, has an imminent role in the prediction of psycho-social adjustment of infertile individuals. Meanwhile, the infertile women showed more negative views in the elements “comparison with fertile people” and “my view toward infertility” but both fertile and infertile subjects did not show any significant differences in psychosocial adjustments. Conclusion: From the three sources of self-knowledge, social comparison, social feedback and self-observation, social comparison plays the first role and social feedback the second in the construction of stigma among infertile people. The results of this study showed the necessity of a health-oriented approach in the evaluation of psycho-social aspects of physical disability among infertile people and also the necessity of modifying and equalizing the functions of the three sources of self-knowledge through group therapy sessions.
Keywords: Infertility, Stigma, Social life, Social comparison